1999
DOI: 10.1021/ja9902975
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic α-Acetoxynitrosamines:  Mechanisms of Decomposition and Stability of α-Hydroxynitrosamine and Nitrosiminium Ion Reactive Intermediates

Abstract: A study of the kinetics and mechanism of the decay of R-acetoxy-N-nitrosopyrrolidine and R-acetoxy-N-nitrosopiperidine are reported. The compounds differ in reactivity by more than 2 orders of magnitude at physiological pH. On the basis of thermodynamic parameters, common ion inhibition and azide ion trapping experiments, both compounds appear to decompose under these conditions by the formation of N-nitrosiminium ion intermediates. The differences in reactivity are rationalized on the basis of results from an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
28
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 28 publications
5
28
0
Order By: Relevance
“…This indicates that the α‐hydrolyzed nitrosamines are more facile to break down to aldehydes and alkydiazohydroxide than CENUs. The experimental results of Fishbein and colleagues lend strong support to this conclusion, which demonstrated that almost all α‐hydroxynitrosamines were unstable in aqueous environments and decomposed spontaneously with a half life of less than 1 min at 37 °C.…”
Section: Resultsmentioning
confidence: 86%
“…This indicates that the α‐hydrolyzed nitrosamines are more facile to break down to aldehydes and alkydiazohydroxide than CENUs. The experimental results of Fishbein and colleagues lend strong support to this conclusion, which demonstrated that almost all α‐hydroxynitrosamines were unstable in aqueous environments and decomposed spontaneously with a half life of less than 1 min at 37 °C.…”
Section: Resultsmentioning
confidence: 86%
“…N-Nitroso-3-Hydroperoxymorpholine (10). The hydroperoxy compound was synthesized by group exchange analogous to what has been reported (29,30,35). To a solution of 9 (30 mg) in 2 mL of MeCN was added 2 mL of 50 wt % H2O2 in water.…”
Section: Methodsmentioning
confidence: 99%
“…The first R-hydroxynitrosamines were synthesized and characterized by Okada, Mochizuki, and co-workers (23)(24)(25)(26). syntheses and study of R-hydroxymethylene-(4) and an R-hydroxymethinyl-nitrosamine (5) have been reported, and these compounds are substantially more reactive, some with millisecond half-lives at neutral pH (27)(28)(29)(30). Among these, the maximum half-life of R-hydroxynitrosopiperidine ( 6) is several seconds at 25 °C (30).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The very high reactivity and the application of organoazides in synthetic chemistry and many important industries [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] has drawn the attention to investigate the structure and conformational behavior of vinyl azide, CH2=CH-NNN [37] and formyl azide, CHO-NNN [38], by DFT and ab initio MP2 calculations. Both molecules were predicted to have a cis/trans conformational equilibrium with the gauche form being the transition state.…”
Section: Introductionmentioning
confidence: 99%